The Emergence of Rod-Cone Cellular Interaction - Aït-Ali, Najate; Léveillard, Thierry (Frontiers in Genetics, 2022)
We studied the origin of rod-derived cone viability factor (RdCVF) during evolution. In mammals, the nucleoredoxin-like 1 gene (NXNL1) produces a truncated thioredoxin-like protein, RdCVF, by intron retention in rod photoreceptors of the retina. This protein prevents the secondary cone degeneration in animal models of rod-cone degeneration. Extracellular RdCVF binds to a complex at the surface of the cones, composed of the basigin-1, a photoreceptor specific alternative splicing product of the basigin gene, and GLUT1, the glucose transporter. RdCVF accelerates glucose uptake allosterically. Glucose is either metabolized by aerobic glycolysis to sustain cone outer segment renewal or by the pentose phosphate pathway to support redox power to the thioredoxin RdCVFL. RdCVF signaling predates the appearance of the eye and evolved through two alternative splicing events. RdCVF signaling is observed first in hydra where it regulates an unknown signaling. A scallop RdCVF protein is produced by ciliated photoreceptors of the retina and binds its receptor, BSG1, the first occurrence of RdCVF/BSG1 signaling. In the lamprey, RdCVF metabolic signaling between rod and cones is fully operational. In the mouse, the production of BSG1 is regulated through alternative splicing. This signaling was extended to other regions of the brain, via its paralogue NXNL2.